The Android game developer's handbook: discover an all in one handbook to developing immersive and cross-platform Android games - Roy, Avisekhar (PACKT Publishing, 2016)
Discover an all in one handbook to developing immersive and cross-platform Android gamesAbout This Book Practical tips and tricks to develop powerful Android games Learn to successfully implement microtransactions and monitor the performance of your game once it's out live. Integrate Google's DIY VR tool and Google Cardboard into your games to join in on the VR revolutionWho This Book Is ForThis book is ideal for any game developer, with prior knowledge of developing games in Android. A good understanding of game development and a basic knowledge on Android platform application development and JAVA/C++ will be appreciated. What You Will Learn Learn the prospects of Android in Game Development Understand the Android architecture and explore platform limitation and variations Explore the various approaches for Game Development using Android Learn about the common mistakes and possible solutions on Android Game Development Discover the top Cross Platform Game Engines and port games on different android platform Optimize memory and performance of your game. Familiarize yourself with different ways to earn money from Android GamesIn DetailGaming in android is an already established market and growing each day. Previously games were made for specific platforms, but this is the time of cross platform gaming with social connectivity. It requires vision of polishing, design and must follow user behavior. This book would help developers to predict and create scopes of improvement according to user behavior. You will begin with the guidelines and rules of game development on the Android platform followed by a brief description about the current variants of Android devices available. Next you will walk through the various tools available to develop any Android games and learn how to choose the most appropriate tools for a specific purpose. You will then learn JAVA game coding standard and style upon the Android SDK. Later, you would focus on creation, maintenance of Game Loop using Android SDK, common mistakes in game development and the solutions to avoid them to improve performance. We will deep dive into Shaders and learn how to optimize memory and performance for an Android Game before moving on to another important topic, testing and debugging Android Games followed by an overview about Virtual Reality and how to integrate them into Android games. Want to program a different way? Inside you'll also learn Android game Development using C++ and OpenGL. Finally you would walk through the required tools to polish and finalize the game and possible integration of any third party tools or SDKs in order to monetize your game when it's one the market!Style and approachThe book follows a handbook approach, focused on current and future game development trend from every possible aspect including monetization and sustainability in the market.